ChemInform Abstract: Poling‐Written Ferroelectricity in Bulk Multiferroic Double‐Perovskite BiFe0.5Mn0.5O3. Issue 34 (4th August 2016) - Delmonte, Davide; Mezzadri, Francesco; Gilioli, Edmondo; Solzi, Massimo; Calestani, Gianluca; Bolzoni, Fulvio; Cabassi, Riccardo
Abstract: Polycrystalline BiFe0.5 Mn0.5 O3 is prepared by hot pressing of stoichiometric amounts of Bi2 O3, Fe2 O3, and Mn2 O3 (Au capsule in multianvil cell, 6 GPa, 1100 °C, 1.5 h).